High-quality development of virtual reality industry from the perspective of environmental regulation - Zhang, Liping; Yang, Yi; Xiong, Kaiqi (Frontiers in Psychology, 2022)
From the perspective of environmental regulation, this paper constructed a high-quality development evaluation system for the virtual reality industry (hereinafter referred to as VRI), calculated the high-quality development level of the VRI, and empirically studied the path of high-quality development of VRI based on the research methods of entropy weight method and structural equation model (hereinafter referred to as SEM), as well as the data of listed companies of VRI in China from 2011 to 2020. The results showed that (1) VRI adapted to the high-quality development level, but there was a certain gap, its high-quality development degree shows a rising trend; (2) the degree of corporate public welfare development had a positive effect on corporate profitability, while the degree of green development and coordinated development had a weak impact on corporate profitability; (3) open and innovative dimensions had a reverse effect on the profitability of enterprises. Enterprises should seek ways to reduce environmental costs and enhance competitiveness. The industrial chain, technology chain and value chain should be constructed to promote the healthy development of VRI and provide support for the formulation of high-quality development policies for VRI.